Pectinolytic and cellulolytic enzyme production by Colletotrichum capsici (Syd.) butler & bisby - Meon, Sariah (Malaysian Society of Applied Biology, 1980)
Using maceration and viscometric tests, culture filtrates and extracts of infected chilli fruits by Colletotrichum capsici were tested for pectinolytic and cellulolytic enzyme production. Maximum activity of both enzymes was observed in 15 day-old cultures. In vivo, activity of both enzymes was maximum in infected fruits 15 days after inoculation, but later it was reduced. A progressive increase in enzyme activity was noted up to 180 min. in the reaction mixture of culture filtrate and extract of fruits obtained 10 days after inoculation.